Effect of Zamzam Water on the Microhardness of Initial Carious Lesion of Permanent Teeth Enamel (An in vitro study) (Mustansiria Dental Journal, 2018)
Chemical tests concluded that Zamzam water is absolutely good and suitable for drinking as it has very high percentage of sodium, calcium, magnesium, and many other minerals. The purpose of this study was to test the effect of Zamzam water on the microhardness of permanent teeth enamel.Teeth samples (n= 30) with artificially initiated carious lesions were divided randomly into three groups, study group treated with Zamzam water (n= 10), control positive treated with sodium fluoride (n=10), and control negative treated with deionized water (n=10). Teeth were subjected for microhardness assessment before and after pH cycling and treatment with the three agents.The microhardness of enamel surfaces treated with Zamzam water is shown statistically significant increase in the values following demineralization which was not different from that of sodium fluoride.Zamzam water cause an increase in the microhardness of the enamel surface after pH-cycling.